PENGARUH KONFLIK PEKERJAAN-KELUARGA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION - Laksana, I.G.N Gede Surya; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 11 (2017), 2017)
Turnover intention is the intention or desire that comes from oneself to move from an old job and looking for a new job that is felt better than the previous one. The main problem of this research is there are problems about turnover intention within employees which is contrary to the three indicators of turnover intention such as there are still employees who are thinking of leaving the company, employees are still eager to find other job vacancies and employees that are thinking about quitting the organization in coming months. The number of samples used as much as 83 respondents. Proportional random sampling was the applied method in this research. Based on the results of multiple linear regression analysis, it was indicated that job-family conflicts have a positive and significant impact on turnover intention, whereas the organizational commitment has a negative and significant effect on turnover intention. The turnover will increase if it is affected by both variables.   Keyword: Work-Family Conflict, Organizational Comitment, Turnover Intention